Environmental stress response limits microbial necromass contributions to soil organic carbon. (June 2015) - Crowther, Thomas W.; Sokol, Noah W.; Oldfield, Emily E.; Maynard, Daniel S.; Thomas, Stephen M.; Bradford, Mark A.
Abstract: The majority of dead organic material enters the soil carbon pool following initial incorporation into microbial biomass. The decomposition of microbial necromass carbon (C) is, therefore, an important process governing the balance between terrestrial and atmospheric C pools. We tested how abiotic stress (drought), biotic interactions (invertebrate grazing) and physical disturbance influence the biochemistry (C:N ratio and calcium oxalate production) of living fungal cells, and the subsequent stabilization of fungal-derived C after senescence. We traced the fate of 13 C-labeled necromass from 'stressed' and 'unstressed' fungi into living soil microbes, dissolved organic carbon (DOC), total soil carbon and respired CO2 . All stressors stimulated the production of calcium oxalate crystals and enhanced the C:N ratios of living fungal mycelia, leading to the formation of 'recalcitrant' necromass. Although we were unable to detect consistent effects of stress on the mineralization rates of fungal necromass, a greater proportion of the non-stressed (labile) fungal necromass C was stabilised in soil. Our finding is consistent with the emerging understanding that recalcitrant material is entirely decomposed within soil, but incorporated less efficiently into living microbial biomass and, ultimately, into stable SOC. Highlights: We show how microbial stress can affect necromass stabilization in soil. Stress increased calcium oxalate production by fungal mycelia. Stress increased carbon concentrations and C:N ratios of fungal necromass. Less of the stressed fungal necromass remained in soil after decomposition. Fungal stress reduced the stabilization of necromass in soil.